National predictors of influenza vaccine uptake in pregnancy: the FluMum prospective cohort study, Australia, 2012–2015. (19th August 2021) - McHugh, Lisa; O'Grady, Kerry‐Ann F.; Nolan, Terry; Richmond, Peter C.; Wood, Nicholas; Marshall, Helen S.; Lambert, Stephen B.; Chatfield, Mark D.; Perrett, Kirsten P.; Binks, Paula; Binks, Michael J.; Andrews, Ross M.
Abstract: Objective : Ascertain predictors of inactivated influenza vaccine (IIV) uptake in pregnancy in mother–infant pairs from six Australian sites over four consecutive influenza seasons (2012–2015). Methods : Prospective observational cohort study calculating proportions of unvaccinated and vaccinated pregnancies. Multivariable logistic regression calculating adjusted odds ratios (aOR) and 95% confidence intervals (95%CI) to determine demographic, pregnancy and birth characteristics as predictors of IIV uptake in pregnancy. Results : Uptake of IIV was 36% (n=3, 651/9, 878) with only 3–4% during the first trimester. Validation of IIV receipt was obtained for 77% of vaccinated participants. Predictors of IIV uptake in pregnancy were: healthcare provider recommendation to have IIV during pregnancy (aOR 7.04 [95%CI 5.83‐8.50]): GP (aOR 4.12 [95%CI 3.43‐4.98]), obstetrician (aOR 4.41 [95%CI 3.45‐5.64]), midwife (aOR 1.88 [95%CI 1.51‐2.36]); previous IIV within 12 months of their current pregnancy (aOR 2.87 [95%CI 2.36‐3.50]); and pertussis vaccination during the current pregnancy (aOR 4.88 [95%CI 4.08‐5.83]). Conclusions and implications for public health : Healthcare provider discussions with pregnant women about the risks associated with influenza infection during pregnancy and early infancy and evidence about the safety and effectiveness of IIV are required. Recommending and offering IIV in pregnancy needs to be included in these discussions to improve uptake.